Students' Perception toward Chat PDF AI Applied in Critical Reading Course - Ni Made Yuniari (Indonesian Postgraduate Foreign Language Education Association, 2024)
Critical reading skills are central to academic achievement since they afford students one capacity to decipher and evaluate texts efficiently. With the entering of Artificial Intelligence (AI) in the education system, new tools have been developed to help in this process, one of which is Chat PDF AI. This qualitative research focuses on the Students at the English Education Department Dwijendra University and their understanding of critical reading courses with the help of Chat PDF AI. The objectives of this study are: to assess the indications of Chat PDF AI on students’ attitude, motivation, and comprehension in critical reading. To achieve the following objectives, a mixed-methods, sequential, explanatory design as highlighted by Creswell, was used. 15 students participated in the study and questionnaires involving structured interviews were used to gather data. The numerical data collected from the questionnaires were computed using descriptive statistics to compare the results for the different variables while the interviews offered more information about the students’ experience and perception regarding the implementation of the ergonomic computer workstations. The findings show that most of the students had a positive perception of chat PDF AI. In detail, 86,7% respondents talked about the improvement in the attitude towards the critical reading because of utilizing the tool; 66,7% respondents stated about their increased motivation as the tool is interactive. According to the qualitative data, the interviewees asserted and supported these discoveries by explaining that Chat PDF AI enhanced the entertaining and interactive attributes of reading tasks, thus making them less monotonous while enabling students to interact in a more productive manner in the learning process. Therefore, Chat PDF AI can be regarded as beneficial in the educational process both impacting the students’ attitudes and their motivation towards critical reading. Thus, although the study’s results appear positive, further research using more significant and diverse groups of participants is required to replicate these outcomes and examine AI tools’ sustained effects on the learners’ performances and critical reading skills.